Synopsis of Sida (Malvoideae, Malvaceae) in the state of Rio Grande do Sul, Brazil - Grings, Martin; Iob Boldrini, Ilsi (Phytotaxa, 2022)
Sida is one of the genera with the highest species richness of Malvaceae and one of the less assessed genera in terms of taxonomy in subfamily Malvoideae. Studies on the taxonomy of the genus in Brazil are scarce. In the state of Rio Grande do Sul Sida is represented by 23 species. This synopsis includes a taxonomic key, illustrations, informations about habitat, maps with geographical distribution, nomenclatural and taxonomic notes, general comments on the biology, ecology and conservation status for all the species. Two names are new synonyms (S. krapovickasii and S. pseudorubifolia), seven names were lectotypified (S. anarthra, S. cerradoensis, S. paradoxa, S. planicaulis, S. riedelii, S. rubifolia, S. viarum), nine species are new records for the state of Rio Grande do Sul (S. cerradoensis, S. confusa, S. cordifolia, S. glaziovii, S. lonchitis, S. nemorensis, S. ramoniana, S. reitzii, S. riedelii). For six species, photos of them in their habitat are presented for the first time, S. farroupilhensis, S. nemorensis, S. paradoxa, S. potentilloides, S. reitzii, and S. rubifolia.